2011
DOI: 10.1063/1.3623762
|View full text |Cite
|
Sign up to set email alerts
|

Finite element method simulation of the domain growth kinetics in single-crystal LiTaO3: Role of surface conductivity

Abstract: Domain growth under the electric field of an atomic force microscope (AFM) is studied by piezoresponse force microscopy in congruent single-crystal LiTaO3 and compared to a finite element method simulation. The model is based on the existence of a conductive top layer, being the water absorbed layer always present in AFM experiments in air, within which the electric potential can propagate beyond the tip contact area. As a result, the simulated domain growth demonstrates kinetics in agreement with experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…The apparent positive correlation between domain size and humidity has been reported previously. [23][24][25]29 However, also contrary observations especially at high humidity have been made, 47,48 which can be attributed to experimental conditions such as samples with higher coercive fields and switching of small sized domains that are more sensitive to the very local redistribution of the electric field caused by the water meniscus and rely less on wide range ionic screening that promotes domain growth. 48 The availability of external screening charge in ambient and humid conditions (OH À on positive domain and H þ on negative domain surfaces) stabilizes newly nucleated domains and facilitates lateral expansion.…”
Section: B Domain Size Thickness and Humidity Dependencementioning
confidence: 76%
See 2 more Smart Citations
“…The apparent positive correlation between domain size and humidity has been reported previously. [23][24][25]29 However, also contrary observations especially at high humidity have been made, 47,48 which can be attributed to experimental conditions such as samples with higher coercive fields and switching of small sized domains that are more sensitive to the very local redistribution of the electric field caused by the water meniscus and rely less on wide range ionic screening that promotes domain growth. 48 The availability of external screening charge in ambient and humid conditions (OH À on positive domain and H þ on negative domain surfaces) stabilizes newly nucleated domains and facilitates lateral expansion.…”
Section: B Domain Size Thickness and Humidity Dependencementioning
confidence: 76%
“…Humidity increases the thickness of this layer and the dimensions of the water meniscus around the tip. 22,24 The water layer has been found to strongly influence ferroelectric switching as it increases the tip-sample capacitance 23 and leads to changes in the field distribution at the tip due to its conductivity [24][25][26] while also providing long range ionic screening charge. [27][28][29] From the qualitative observation that domain walls appear wider at high humidity than in dry conditions (Figure 2), a larger size of the "top electrode" consisting of tip and water meniscus can be inferred.…”
Section: B Domain Size Thickness and Humidity Dependencementioning
confidence: 99%
See 1 more Smart Citation
“…41 It was shown experimentally that that the sample surface is covered by thin water layer for switching in ambient conditions. 43,44 Thus, the obtained time dependences of the domain sizes depend significantly on the humidity. 45,46 Following this approach, we rationalized the evolution of the domain radius with time in our case as…”
Section: B Local Switching and Domain Wall Motionmentioning
confidence: 99%
“…Different explanations have been proposed for the actual mechanism that leads to a change in the electric field: static finite-element simulations studies have suggested that the water meniscus could act as an effective electrode, 156 while similar simulations with an additional time evolution reported a slow lateral propagation of the electric field. 157 Recent studies addressing both relative humidity and the effects of switching voltage pulse sequence 158 highlight the necessity to incoroporate environmental contributions to field modelling.…”
Section: Effects Of Environmentmentioning
confidence: 99%